Towards First-Class Architectural Connectors: The Case for Self-Adaptive Service Meshes - Mendonca, Nabor; Aderaldo, Carlos (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2021: Anais do XXXV Simpósio Brasileiro de Engenharia de Software, 2021)
The development of architectural connectors as first-class software entities is a long-standing software engineering promise that has not been fully realized thus far. This observation is especially true in self-adaptive software systems, where most advances within academia and industry have targeted software components as the primary locus for run-time adaptation. In this paper, we revisit the evolutionary history of architectural connectors and discuss the challenges of implementing architectural connectors as first-class self-adaptation entities in the domain of modern microservice applications. We then make a case for our ongoing work on a cloud-native self-adaptive service mesh framework that builds on recent container orchestration, self-adaptation, and service mesh technologies.